TIPE2 Suppresses Malignancy of Pancreatic Cancer Through Inhibiting TGFβ1 Mediated Signaling Pathway - Feng, Fang; Liu, Chunliang; Bian, Huahui; Cai, Wei; Zhou, Ying; Zhou, Li; Zhuang, Zhixiang (Frontiers in Oncology, 2021)
Pancreatic cancer is one of the major reasons of cancer-associated deaths due to poor diagnosis, high metastasis and drug resistance. Therefore, it is important to understand the cellular and molecular mechanisms of pancreatic cancer to identify new targets for the treatment. TIPE2 is an essential regulator of tumor apoptosis, inflammation and immune homeostasis. However, the role of TIPE2 is still not fully understood in pancreatic cancer. In this study, we found the expression of TIPE2 was decreased in pancreatic cancer tissues compare to paracancerous tissues, which was negatively correlated with tumor size in patients. Overexpression of TIPE2 significantly decreased cell proliferation, metastasis and increased apoptotic events in pancreatic cancer cell lines. Moreover, the results obtained from real time PCR and western blot revealed that TIPE2 was also involved in inhibiting MMPs and N-Cadherin expression while increasing Bax expression in pancreatic cancer cells. Similarly, TIPE2 could inhibit tumor growth in vivo, decrease the expression of Ki-67 and N-Cadherin, and increase the expression of Bax by IHC analysis in tumor tissues isolated from tumor-bearing mice. Mechanistic studies exhibited that TIPE2 might suppress pancreatic cancer development through inhibiting PI3K/AKT and Raf/MEK/ERK signaling pathways triggered by TGFβ1. Moreover, the tumor-infiltrating lymphocytes from tumor-bearing mice were analyzed by flow cytometry, and showed that TIPE2 could promote T cell activation to exert an anti-tumor effect possibly through activation of DCs in a TGFβ1 dependent manner. In general, we described the multiple regulatory mechanisms of TIPE2 in pancreatic tumorigenesis and tumor microenvironment, which suggested TIPE2 may act as a potential therapeutic target in pancreatic cancer.